Investigation on the effects of cooling rate on surface Texture, corrosion behaviour and hardness of pure copper - Nikhil; Kumar Singh M.; Ji G.; Prakash R. (My University, 2025)
Present work deals with the intentional water quenching treatment of copper and investigation of the changes in its surface texture, hardness and corrosion behavior. Copper strips are heated to 400 C and 600 C followed by immediate immersion in water at room temperature. Due to this treatment, drastic change in the surface texture of copper has occurred, which are monitored by high resolution scanning electron microscope (HRSEM). The corrosion investigation has been done by electrochemical impedance spectroscopy (EIS), whereas hardness is measured by vicker' hardness tester. Surprisingly, both hardness and corrosion resistance is reduced after this treatment; however, reduction is not eventuated in the same ratio. This fact establishes a direct relation of hardness with corrosion resistance for copper and indicates reduction in both by water quenching. © 2020 Elsevier Ltd. All rights reserved.